PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION TERHADAP HASIL BELAJAR SISWA KELAS X PADA MATA PELAJARAN MENERAPKAN DASAR-DASAR TEKNIK DIGITAL TEKNIK AUDIO VIDEO DI SMKN 1 BATIPUH - Wonang Saputra; Thamrin Thamrin; Almasri Almasri (Universitas Negeri Padang, 2017)
The problem in this study is the low average learning outcomes of students on subjects Applying Digital Engineering Basics is under the Minimum Criterion of completeness which has been established SMKN 1 Batipuh is 75. This study aims to determine the effect of application of Team Assisted Individualization model to learning outcomes on subjects Applying Digital Engineering Basics in Audio Video Techniques department at SMKN 1 Batipuh. The type of this research is experimental research with pre experimental design with intact group comparison design. The sample of research is class X TAV 2A as experiment class using Team Assisted Individualization model and class X TAV 2B as control class using direct learning model. Data is collected from post-test in the experimental class and control class, then analyzed for homogeneity, normality and hypothesis test. From the experimental class results obtained an average value of 80.71, while the control class gets an average value of 75.79. The result of hypothesis calculation at significant level α = 0,05 got tcount> ttable that is 2,442 > 2,056, because big tcount of ttable, null hypothesis (H0) rejected and alternative hypothesis (Ha) accepted.itCan be concluded mean at the real level, this research shows that, there is work on of student learning result which signifikan between usage of Team Assisted Individualization type with direct learning model on subjects Applying Digital Engineering Basics of student of Audio Video Technique at SMKN 1 Batipuh. So the Team Assisted Individualization learning model is better than the direct learning model. Keywords: Applying Digital Engineering Basics, Team Assisted Individualization model, direct learning model, pre experimental design, learning outcomes.